Local wisdom-oriented learning module to improve mathematical creative thinking ability of dyscalculia students - Purwaningrum, Jayanti Putri; Muzid, Syafiul; Siswono, Tatag Yuli Eko; Masriyah, Masriyah (Linguistics and Culture Review, 2021)
This study aims to examine the effectiveness and the positive responses given by dyscalculia students and teachers toward a module oriented to Kudus’ local wisdom to improve the mathematical creative thinking ability of dyscalculia students. This research was conducted in Kudus Regency, Central Java, Indonesia with 75 fourth graders from eight different elementary schools as the subject of the study. The model used in the teaching materials development is the Dick & Carey model. The results showed that the local wisdom-oriented module which was developed according to the experts is excellent. In addition, the results of the Pre-test and Post-test showed that there is an increase in the mathematical creative thinking ability of dyscalculia students. Meanwhile, the results of interviews and questionnaires showed that teachers and dyscalculia students give positive responses to the use of modules oriented to Kudus’ local wisdom.